Optimalisasi Layanan Publik Melalui Pelatihan Sistem Administrasi Digital - Sukiman, Sukiman; Nistrina, Khilda; Sutiyono, Sutiyono (Universitas Negeri Gorontalo, 2025)
Data management and health administration reporting by the cadres of Posyandu Mawarsari 6 still rely on manual recording, which poses risks of data loss, information duplication, and delays in monthly reporting. This activity aims to improve the digital skills of 15 posyandu cadres in data management and administration through the use of digital technology. The method involved staged training on the use of Google Forms for participant registration, Google Drive for document storage and management, and Microsoft Excel for data processing and report creation. The activity was conducted in three phases: preparation, implementation, and evaluation. The training results showed significant improvement, with 87% of cadres able to independently create digital forms, 80% able to manage cloud-based documents, and 90% able to compile digital health reports effectively. The implementation of this digital administration system proved to increase work efficiency, data accuracy, and reduce dependence on manual systems. This underscores the importance of digital literacy in supporting the transformation of community-based health services at the posyandu level.